The Clinical Features and Expression of bcl-2, Cyclin D1, p53, and Proliferating Cell Nuclear Antigen in Syndromic and Nonsyndromic Keratocystic Odontogenic Tumor. Issue 5 (July 2016) - Ibrahim, Norliwati; Nazimi, Abdul Jabar; Ajura, Abdul Jalil; Nordin, Rifqah; Latiff, Zarina Abdul; Ramli, Roszalina
Abstract : Abstract: The aim of this study was to describe the clinical features and expression of bcl-2, cyclin D1, p53, and proliferating cell nuclear antigen (PCNA) antibodies in syndromic (nevoid basal cell carcinoma syndrome [NBCCS]) and nonsyndromic patients diagnosed with keratocystic odontogenic tumor (KCOT). Methods: This descriptive study comprised 5 patients of KCOT associated with NBCCS and 8 patients of nonsyndromic type treated in the Department of Oral Maxillofacial Surgery, Universiti Kebangsaan Malaysia Medical Centre between years 1998 and 2011. The clinical features (site, size, treatment, and recurrence), demographic characteristics, and immunohistochemistry results using antibodies of bcl-2, cyclin D1, p53, and PCNA were examined. The association of the antibody expression and the type of KCOT was analyzed using Fisher exact test. Results: Altogether there were 13 patients, 5 with syndromic KCOT (1 patient met 3 major criteria of NBCCS) and 8 with sporadic KCOT. The age range for syndromic KCT was 11 to 21 years (mean 16.00 years, SD 4.36) and 10 to 54 years (median 24.50 years, interquartile range 19.00) for the nonsyndromic KCOT. Tumor recurrence occurred in 3 patients (7.7%); 1 patient from the syndromic and 2 patients from the nonsyndromic. The most positive expression was observed in PCNA for both the syndromic and nonsyndromic samples and the least positive expression involved the p53. Conclusion: PCNA, bcl-2 protein, and cyclin D1 expressions could be useful in evaluating the proliferative activity of the tumor and the aggressiveness of the clinical presentation; however, the authors would propose for larger sample size research for more definitive results.